El acondicionamiento físico y la relación con el estrés en los Policías Nacionales del Distrito Metropolitano de Quito (Physical conditioning and the relationship with stress in the National Police of the Metropolitan District of Quito) - Pineda Calderón, Christian Fernando; Monteros Luzuriaga, Guillermo Salvador; Yepez Herrera, Emerson Roberto; Guerron Varela, Edgar Ramiro (Retos, 2023)
La actividad física es un medio que permite mejorar el estado de salud y el control del estrés laboral aportando energía a las rutinas diarias de la vida. Esta investigación tiene como objetivo analizar la relación entre la condición física y el nivel de estrés que manejan los Policías Nacionales de diversas unidades acantonadas en el Distrito Metropolitano de Quito, a través de un plan de acondicionamiento físico y psicológico de un mes de duración. Esta investigación es de tipo cuasi experimental y correlacional con una muestra de 68 efectivos policiales en servicio activo seleccionados aleatoriamente donde 59 policías fueron hombres y 9 mujeres. Para la recolección de la información se aplicó varios test dados en do tiempos un pre y post tes: test abdominal, test de resistencia, test de velocidad y la prueba de estrés laboral adaptado del cuestionario de problemas psicosomáticos, los cuales permitieron obtener resultados significativos en la mejora de condición física y el manejo de estrés.Palabras clave: Acondicionamiento físico, estrés laboral, OMS, Policía Nacional, salud.Abstract. Physical activity and control of work stress are essential instruments to improve health status; The objective of this research was to analyze the relationship between physical condition and the level of stress handled by the National Police of various units that provide their services in the Metropolitan District of Quito, through the application of a physical and psychological conditioning plan of a month, based on the standards of the World Health Organization with a level of moderate-vigorous physical activity, combined with force, in which 68 police officers participated, of whom 59 were men and 9 women, randomly selected, whose average age was 35 years, under two systems of face-to-face and virtual participation. Variables were measured such as: body mass index (BMI), physical condition measured through capacity tests (strength, endurance, and speed), and work stress, the same that was applied before and after undergoing the planned plan. In the statistical analysis it was possible to find significant differences in his physical condition through the BMI indicators, decreasing the average from 31.2 to 30.5, concerning his psychological stability went from 13.1 to 11.2, and finally an improvement in his physical performance from 34.7 to 40.5 sit-ups per (min), in the course of a mile the time decreased from 10.9 (min) to 9.8 (min) and in speed, the average time improved from 16.1 (s).  to 14.6 (s), it was also possible to identify that there are no significant differences by sex or training modality.Keywords: Physical conditioning, work stress, WHO, National Police, health.